EFFECT OF ECONOMIC AND PSYCHOLOGICAL FACTORS ON PURCHASING DECISIONS ON TOYOTA BRAND CARS - Ratnawita, Ratnawita; Ninik Churniawati; Yusnaena, Yusnaena; Yofina Mulyati; Syamsulbahri (Journal of Innovation Research and Knowledge, 2023)
This study aims to determine and analyze effect of economic and psychological factors on purchasing decisions on Toyota brand cars. The type of research used in this research is quantitative analysis research. Population of this research is 200 buyers of Toyota brand cars. Sample size of this research is 100 buyers. Hypothesis testing uses a multiple linear regression model. The results show that economic factor has a positive and significant effect on purchasing decisions on Toyota brand cars. Psychological factor has a positive and significant effect on purchasing decisions on Toyota brand cars.